'Groupthink'to 'Teamthink' : Creation of Constructive Thought Patterns in Participatory forest Management - Kinhal, G. A. (Indian Forester, 2002)
Controversy and conflict over resource decisions appear to be intensifying and as a result, issues critical to the uation's future are avoided, energy is dis,ipated, and everyone involved loses credibility. Currently, the tendency is to blame the management agencies for all resource maladies. Parties involved in the conflict, such as environmentalists, stakeholders and local dependants typically view opponents as the source of problem and spurn responsibility for finding solutions As a matter of fact, the forestry agencies, having taken this responsibility, are trying to find solutions to counter the allegation. This paper argues that the solution to above problem lies in converting the current participatory mode from a "group think" method to a "Teamthink" method. Such a shift should enhance the success of participation leading to better conservation of natural resource.